2020
DOI: 10.1093/jee/toaa116
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Temperature and Humidity on a Field Population of Bradysia odoriphaga (Diptera: Sciaridae)

Abstract: The production of Chinese chives is reduced throughout China due to a root-feeding dipteran pest Bradysia odoriphaga Yang et Zhang (Diptera: Sciaridae), therefore deciphering the conditions influencing its growth and development are important in developing ecological control strategies. A study was conducted from 2014 to 2017 to determine the relationship between the abundance of B. odoriphaga and temperature (atmospheric and soil), soil water content, and atmospheric humidity in a Chinese chive field in Beiji… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…This indicated that extreme temperatures not only restricted the growth and infection of the fungus, but also accelerated nutrient metabolism resulting in less extracellular enzymes and toxic proteins ( Bai et al 2016b ). Previous studies reported that during the emergence peak of B. odoriphaga larvae, the mean soil temperature fluctuates between 15 and 25°C, which would be suitable for the use of M. hiemalis BO-1 to control B. odoriphaga based on our results ( Shi et al 2018 , 2020 ). To sum up, M. hiemalis BO-1 application could provide satisfactory control efficiency during the spring and autumn in open fields, or during winter in the greenhouse.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This indicated that extreme temperatures not only restricted the growth and infection of the fungus, but also accelerated nutrient metabolism resulting in less extracellular enzymes and toxic proteins ( Bai et al 2016b ). Previous studies reported that during the emergence peak of B. odoriphaga larvae, the mean soil temperature fluctuates between 15 and 25°C, which would be suitable for the use of M. hiemalis BO-1 to control B. odoriphaga based on our results ( Shi et al 2018 , 2020 ). To sum up, M. hiemalis BO-1 application could provide satisfactory control efficiency during the spring and autumn in open fields, or during winter in the greenhouse.…”
Section: Discussionsupporting
confidence: 51%
“…Bradysia odoriphaga is an underground insect in its immature stages and adults leave the soil. However, during the emergence peak of B. odoriphaga , the mean soil temperature in fields is typically below 20°C, which is not optimal for many biological insecticides ( Shi et al 2020 ). To sum up, finding an entomopathogenic fungus possessing high pathogenicity and broad environmental adaptability for use against B. odoriphaga appears to be key to improving biocontrol efficiency.…”
mentioning
confidence: 99%
“…37 A high drought in summer will cause a sharp decline in the population of B. odoriphaga. 37 2.1.5 Research method 2.1.5.1. Parameters for Bradysia odoriphaga.…”
Section: Methodsmentioning
confidence: 99%
“…B. odoriphaga larvae mainly live in the soil at a depth of 0–5 cm. They can develop in a soil moisture range of 12.5–48% 37 . A high drought in summer will cause a sharp decline in the population of B. odoriphaga 37 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation